2023
DOI: 10.2147/idr.s413416
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dietary Approach with Probiotics, Prebiotics, and Synbiotics to Mitigate Antimicrobial Resistance and Subsequent Out Marketplace of Antimicrobial Agents: A Review

Abstract: Antimicrobial resistance (AMR) is a significant public health concern worldwide. The continuous use and misuse of antimicrobial agents have led to the emergence and spread of resistant strains of bacteria, which can cause severe infections that are difficult to treat. One of the reasons for the constant development of new antimicrobial agents is the need to overcome the resistance that has developed against existing drugs. However, this approach is not sustainable in the long term, as bacteria can quickly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…The current landscape of antimicrobial development is characterized by significant risks, primarily stemming from the time-consuming and expensive nature of the process . However, a promising alternative approach involves repurposing existing non-antibacterial drugs for antibacterial purposes, which has emerged as a cost-effective strategy in recent years. , Our prior investigation demonstrated that modifications to the side-chain carbamate moiety of loratadine and its derivatives resulted in the inhibition of biofilm formation, pigmentation, and hemolysis in Staphylococcus aureus .…”
mentioning
confidence: 99%
“…The current landscape of antimicrobial development is characterized by significant risks, primarily stemming from the time-consuming and expensive nature of the process . However, a promising alternative approach involves repurposing existing non-antibacterial drugs for antibacterial purposes, which has emerged as a cost-effective strategy in recent years. , Our prior investigation demonstrated that modifications to the side-chain carbamate moiety of loratadine and its derivatives resulted in the inhibition of biofilm formation, pigmentation, and hemolysis in Staphylococcus aureus .…”
mentioning
confidence: 99%